2011
DOI: 10.1371/journal.pone.0017749
|View full text |Cite
|
Sign up to set email alerts
|

Natural Gaits of the Non-Pathological Flat Foot and High-Arched Foot

Abstract: There has been a controversy as to whether or not the non-pathological flat foot and high-arched foot have an effect on human walking activities. The 3D foot scanning system was employed to obtain static footprints from subjects adopting a half-weight-bearing stance. Based upon their footprints, the subjects were divided into two groups: the flat-footed and the high-arched. The plantar pressure measurement system was used to measure and record the subjects' successive natural gaits. Two indices were proposed: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 24 publications
0
26
0
3
Order By: Relevance
“…Fan et al . () compared the non‐pathological flat foot vs. high‐arched foot of adults during gait; they found that there was a significant difference in the distributions of vertical force and in the rate of change of footprint area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fan et al . () compared the non‐pathological flat foot vs. high‐arched foot of adults during gait; they found that there was a significant difference in the distributions of vertical force and in the rate of change of footprint area.…”
Section: Discussionmentioning
confidence: 99%
“…pathological conditions. The studies on this topic have been conducted on healthy individuals during walking (Lin et al 2001;Levinger et al 2010;Fan et al 2011;Shih et al 2012). Lin et al (2001) and Shih et al (2012) demonstrated that movement patterns at main lower limb joints during gait were in general similar between children with and without flat foot.…”
Section: Group With Low Archmentioning
confidence: 99%
See 1 more Smart Citation
“…X-rays and computed tomography (CT) have been employed as the clinical image rating systems [5][6][7][8]. Radiographs taken under weight bearing have been reported to be useful for evaluation of stage II PTTD flatfoot deformity as well as preoperative planning of flatfoot corrective surgery [7,9]. While there are numerous radiographic studies using plain X-rays, including measuring the talonavicular coverage angle, talo-first metatarsal angle, and calcaneal pitch to evaluate flatfoot deformity [5,10], CT is reported to be more accurate for assessing the relationship of complicated tarsal bones as compared with plain X-rays [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The excessive amount of weight is placed on ball and heel of the foot when walking or standing [2]. Arches can be so high that you are only walking on your bone structure, heel, ball and toes; all pressure areas observed in foot prints taken.…”
Section: Resultsmentioning
confidence: 99%